2011
DOI: 10.1007/s12678-011-0054-1
|View full text |Cite
|
Sign up to set email alerts
|

Determining the Active Surface Area for Various Platinum Electrodes

Abstract: Various methods, i.e., the adsorption/stripping of adsorbed probe species, such as hydrogen (H), copper (Cu), and carbon monoxide (CO), oxygen and hydroxide (O/ OH), potentiostatic CO/H displacement as well as double layer capacitance are exploited to evaluate the electrochemically active surface areas (ECAs) of platinum (Pt) foils, chemically deposited Pt thin film, and carbon-supported Pt nanoparticle electrodes. For the relatively smooth Pt electrodes (roughness factor < 3), the measurements from the stripp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
96
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 166 publications
(109 citation statements)
references
References 46 publications
(91 reference statements)
7
96
0
2
Order By: Relevance
“…Carbon monoxide (CO) can be used for this purpose because it is a strong adsorbent which also displaces other adsorbed species from the surface site and therefore can be used for the EASA determination as well as cleaning the electrode surface [19][20][21]. Firstly, the electrolyte is saturated with CO gas which is rapidly adsorbed on the Pt surface.…”
Section: Electrochemically Active Surface Areamentioning
confidence: 99%
“…Carbon monoxide (CO) can be used for this purpose because it is a strong adsorbent which also displaces other adsorbed species from the surface site and therefore can be used for the EASA determination as well as cleaning the electrode surface [19][20][21]. Firstly, the electrolyte is saturated with CO gas which is rapidly adsorbed on the Pt surface.…”
Section: Electrochemically Active Surface Areamentioning
confidence: 99%
“…3). The EASA has been determined [42] from the hydrogen adsorption and desorption charge after stabilization (10 cycles). Table 1 shows that even the samples treated with the shorter wave period (6 min) the EASA is enhanced by a factor 2.45.…”
Section: Resultsmentioning
confidence: 99%
“…The electrochemically active surface area (EASA) of this electrode was determined by integration of the charge in the hydrogen region of the cyclic voltammograms (CVs) between 0.05 and 0.4 V in 0.5 M H 2 SO 4 solution [42]. The activity for ethanol oxidation was investigated in 2 M ethanol + 2 M KOH by cyclic voltammetry between 0.05 and 0.70 V. All of the CVs were repeated until curves were obtained with high stabilization.…”
Section: Methodsmentioning
confidence: 99%
“…The scan rate chosen for these measurements (10 mV/s) is appropriate according to the work of Chaparro et al [46]. In a recent study [47], it was concluded that, if a negative potential limit for integration equal to 0.05 V RHE is chosen, a charge of 0.22 mC would correspond to 1 cm 2 of Pt electrochemically active area. In our case, a potential of 0.05 V RHE corresponds to a potential of −0.17 V versus Ag/AgCl, which was chosen as the negative limit for voltammogram integration.…”
Section: Resultsmentioning
confidence: 99%